How considerate are the Arabic language Textbooks For The Fourth, Fifth and Sixth Grades to Moral Values In Jordan: An Analytical Study - Eman Ababneh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This research aims to explore how considerate are the Arabic language textbooks for the fourth, fifth and sixth grades to the Moral values in Jordan. To achieve this analytical approach, It was based on the analysis of the Arabic Language Textbooks for the fourth, fifth and sixth grades in schools affiliated with the Jordanian Ministry of Education for the academic year 2018/2019, and has identified for this the clear picture and sentence to be a unit of analysis. The researcher prepared a list of Moral values as a tool for these study, after verifying their validity and stability, to analyze the content of these textbooks. The results of this study showed that the total number of repetitions of Moral values in the Arabic language Textbooks - the sample of these study - reached (1681) values and by a percentage of (56%). and most of these textbooks were concerned with moral values, The Arabic Language textbook for the sixth grade, as the inclusion of the values reached (59.5%), Followed by the fifth grade textbook (56%), and finally the textbooks of the fourth grade (52.6%). And the highest values in these textbooks were the value of (respect for science and scientists), It was repeated (164) values. And the least it (Remove the damage and Al-helm) 3 values in these textbooks.